Makna Leksikal dan Gramatikal pada Judul Berita Portal Detik.com Edisi November 2025 di Media Sosial Instagram - Lingga Wulandari; Desma Yuliadi Saputra; Rina Andriani (Asosiasi Periset Bahasa Sastra Indonesia, 2026)
This study examines the lexical and grammatical meanings of news headlines from the November 2025 edition of detik.com, posted on Instagram. The shift from a news site to a social media platform often necessitates adjustments to headlines, which can lead to shifts in meaning. To collect relevant headlines, this study employed a qualitative descriptive method with a listening and note-taking technique. The analysis shows that lexical meaning in headlines is evident through the use of words with basic dictionary meanings, such as names of people, places, objects, and actions. Grammatical meaning is discovered through affixation and reduplication, which can change or add to the meaning of basic words according to the context. These two types of meaning play a crucial role in creating concise, clear headlines that are appropriate for the way news is presented on Instagram. This study concludes that the formation of meaning in headlines on detik.com is influenced by a combination of lexical and grammatical meanings tailored to the communication needs of social media platforms.